TEACHING INTERCULTURAL COMPETENCE THROUGH AUTHENTIC VIDEO MATERIALS IN EFL CLASSROOMS - Shamsutdinova Lyutsiya Rafailovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. In contemporary English as a Foreign Language (EFL) education, intercultural communicative competence has become a key objective of language instruction. This article explores the role of authentic video materials in fostering intercultural awareness, pragmatic competence, and communicative effectiveness. Drawing on recent scholarly literature, the paper analyzes how audiovisual input provides learners with access to real-life language use and culturally embedded meanings.A structured instructional framework and practical classroom applications are proposed. The study argues that authentic video materials serve as an effective pedagogical tool for integrating linguistic and cultural learning, thereby enhancing learners’ ability to communicate appropriately in intercultural contexts.